Morphology and pore size distribution of electrospun and centrifugal forcespun nylon 6 nanofiber membranes. Issue 12 (July 2016) - Krifa, Mourad; Yuan, Wei
The porosity and high surface-area-to-volume ratio of nanofiber membranes offer potential for diverse applications, including high-efficiency filters and barrier fabrics for use in protective textiles. The objective of this research is to examine the morphology and pore size distribution of nanofiber membranes prepared using two spinning methods, that is, electrospinning and forcespinning. The results indicate that fiber diameter is impacted by spinning solution viscosity in an analogous way for both spinning methods. Higher concentrations resulted in larger fiber diameters in both electrospun and forcespun membranes. Fiber diameter and membrane areal density were found to significantly impact membrane pore size distribution. A theoretical model was used to describe pore size variation and was found to agree with the empirical patterns in the case of electrospun membranes.